2016
DOI: 10.1371/journal.pone.0163672
|View full text |Cite
|
Sign up to set email alerts
|

Maternally Derived Immunity Extends Swine Influenza A Virus Persistence within Farrow-to-Finish Pig Farms: Insights from a Stochastic Event-Driven Metapopulation Model

Abstract: Swine Influenza A Viruses (swIAVs) have been shown to persist in farrow-to-finish pig herds with repeated outbreaks in successive batches, increasing the risk for respiratory disorders in affected animals and being a threat for public health. Although the general routes of swIAV transmission (i.e. direct contact and exposure to aerosols) were clearly identified, the transmission process between batches is still not fully understood. Maternally derived antibodies (MDAs) were stressed as a possible factor favori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 41 publications
2
22
0
Order By: Relevance
“…This study documented IAV persistence within a swine herd over a one-year period, supporting the increasing number of studies that have shown that IAV may persists within the herd [38][39][40][41][42][43][44][45]. Furthermore, the study confirms previous studies documenting a lack of seasonality of swIAV infections [28,80].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study documented IAV persistence within a swine herd over a one-year period, supporting the increasing number of studies that have shown that IAV may persists within the herd [38][39][40][41][42][43][44][45]. Furthermore, the study confirms previous studies documenting a lack of seasonality of swIAV infections [28,80].…”
Section: Discussionsupporting
confidence: 89%
“…Over the past ten years, the understanding of swIAV circulation in swine herds has changed and it is now recognized that an infection with swIAV is likely to result in an enzootic infected herd [38][39][40][41][42][43][44][45]. This is probably a consequence of increasing herd sizes, which provides a continuous flow of naïve piglets [46,47].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, it is difficult to assess what impact neglecting a more complex herd structure would have on our model outputs. Previous studies have examined disease dynamics in smaller structured populations using a metapopulation approach [44]. Alternatively, models could also be stratified by age or level of risk to capture heterogeneity in host contacts.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of swine flu, it has been shown recently in a transmission experiment involving piglets born to vaccinated or non-vaccinated sows that the presence of maternally derived antibodies in piglets significantly decreased the virus transmission but not enough to block its propagation within the population. Moreover, the transmission intensity in this immunized population born to vaccinated sows was slowed down, increasing the total duration of the infectious process within the population and enhancing potentially the enzootic persistence of the virus in the farm [19, 20]. …”
Section: Source Of Variation Of Vaccine Efficacy and Practical Conseqmentioning
confidence: 99%